Granulicatella adiacens Subacute Bacterial Endocarditis Presenting as Diffuse Alveolar Hemorrhage and Infection-Related Glomerulonephritis - Kevin Dao; Pooja Patel; Kunjan Udani; Erin Pollock; Maryam Gondal (Case Reports in Infectious Diseases)
We present a case of a 69-year-old male with a past medical history of prostate cancer, chronic mitral valve regurgitation, and recent dental cleaning who presented to the hospital with shortness of breath, anemia, and acute renal failure. Due to unexplained creatinine rise, a renal biopsy was obtained which was suspicious for infection-related glomerulonephritis (IRGN). Further workup confirmed subacute endocarditis according to modified Duke’s criteria. The patient’s blood culture became positive for Granulicatella adiacens, a nutritionally variant streptococcus. The patient later developed acute respiratory failure from diffuse alveolar hemorrhage (DAH). Subacute infective endocarditis can result in serious morbidity and mortality due to its insidious symptoms and subsequent fatal complications.